The Effect of Aromatherapy Massage With Lavender Oil On Pain Levels and Quality Of Life in Diabetic Neuropathy Patients - Kholifah, Nevia; Purnama, Agus; Afrina, Rina (Open Access Health Scientific Journal, 2025)
Background: Diabetes Mellitus has increased significantly worldwide. Diabetes is a A metabolic disease characterized by hyperglycemia. Diabetic neuropathy pain is a complication of diabetes. Reducing pain is essential to improving the quality of life of patients with diabetic neuropathy. This study aimed to determine the effect of aromatherapy massage with lavender oil on pain levels and quality of life in diabetic neuropathy patients at Cengkareng Regional Hospital.Methods: This research design is a quantitative study with a Quasy Experiment approach with one equivalent control group pretest-posttest design. Data collection using VAS and WHO-QOL questionnaires. Data analysis was performed univariately and bivariately with the Shapiro Wilk test using Jamovi 2.3.28 software.Results: There was a difference in pain levels before and after being given aromatherapy massage with lavender oil in diabetic neuropathy patients with a P value of 0.017 with an effect size of 1.22. Meanwhile, for the quality of life of diabetic neuropathy patients, a P value of 0.274 was obtained, indicating that there was no difference in the level of quality of life of patients after being given aromatherapy massage with lavender oil with an effect size of 0.494.Conclusion: It is hoped that aromatherapy massage with lavender oil can be used as input for health services in reducing pain levels and improving the quality of life of diabetic neuropathy patients